Another kind of madness : a journey through the stigma and hope of mental illness - Hinshaw, Stephen P. (St. Martin's Press, 2017)
"Families are riddled with untold secrets. But Stephen Hinshaw would have never thought that in his family a profound secret had been kept under lock and key for 18 years. From the moment his father revealed his long history with mental illness and involuntary hospitalizations, Hinshaw knew his life would be changed forever. Hinshaw calls his father's reveal "psychological birth"--after years of experiencing the ups and downs of his father's illness without knowing it existed, watching him disappear for weeks at a time only to return as the loving father he had always known, everything he experienced as a child began to make sense. He learned as much as possible about his father's illness, and what began as an exploration into his father's past and mental health turned into a full-fledged career as a clinical psychologist. In Another Kind of Madness, Hinshaw explores the burden of living in a family "loaded" with mental illness and debunks the "stigma" behind it, explaining that in today's society, mental health problems can result in a loss of a driver's license, inability to vote or run for office, ineligibility for jury service, or automatic relinquishment of child custody. With a moving personal narrative and shocking facts about how America views mental health conditions in the 21st century, Another Kind of Madness is a passionate call to arms regarding the importance of destigmatizing mental illness"--